A Comparison of the Implementation of the Merdeka Curriculum in Indonesia and The National Curriculum in England in Developing 21st Century Skills - Sari, Linda Nevia; Fakhruddin, Fakhruddin; Asha, Lukman (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study examines the implementation of the Merdeka Curriculum in Indonesia and the National Curriculum in England in developing 21st-century skills. Through a systematic literature review of policy documents, reports from educational institutions, and recent empirical studies, the analysis focuses on three main aspects: the philosophical and conceptual orientation of both curricula, the recommended teaching approaches for their implementation, and the assessment mechanisms used to evaluate student competence development. The findings show that the Merdeka Curriculum emphasizes pedagogical flexibility, contextual learning, and project-based activities aimed at fostering independence and character development. In contrast, the National Curriculum in England is characterized by more structured learning achievement standards, clear implementation guidelines, and a well-established system of professional development and accountability. Despite having different orientations, both curricula prioritize strengthening critical thinking, creativity, communication, and collaboration skills. The study also highlights that the effectiveness of a curriculum is not only determined by its design but also by the institutional capacity and teacher readiness to translate it into practice. Variations in school resources and educator professional competencies pose specific challenges in Indonesia, while England benefits from a long-established supporting structure. Overall, the findings affirm the importance of aligning curriculum flexibility with consistent policy support to ensure meaningful development of 21st-century skills.